2012
DOI: 10.5751/es-04642-170214
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of the Use of Eucalyptus Biomass for Energy on Wood Availability for Eucalyptus Forest in Portugal: a Simulation Study

Abstract: ABSTRACT. In the scope of energy diversification and profitable forest resource exploitation, increasing the use of biomass residues for energy can play an important role by using local sources of energy, reducing carbon emissions and fossil-energy use, providing additional revenue for the forest sector, and also reducing the risk of forest wildfires. Regional simulators can help forecast available wood and biomass and allow evaluation of possible future conflicts of interest and their consequences for society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The stands are normally exploited with three cutting cycles, and at the end of the commercial exploitation, the plantations must be re-established and the stumps removed prior to soil preparation (Barreiro and Tomé 2012;Soares and Tomé 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The stands are normally exploited with three cutting cycles, and at the end of the commercial exploitation, the plantations must be re-established and the stumps removed prior to soil preparation (Barreiro and Tomé 2012;Soares and Tomé 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While eucalyptus plantations in the study region currently serve multiple markets, including domestic timber needs and charcoal trade to Sudan, the presence of plantation forests does address local energy need to some extent. Studies of eucalyptus growing regions in Ethiopia have indicated that on the order of half of the harvested eucalyptus biomass is used locally for energy and other uses (e.g., Barreiro and Tomé, 2012;Berhanu et al, 2017).…”
Section: Implications For Food Energy and Water Resourcesmentioning
confidence: 99%
“…SIMPLOT is a non-spatialized regional simulator based on inventory plots (Barreiro and Tomé, 2011;Barreiro and Tomé, 2012), designed to predict longterm development of all stands in a region taking into account the following external drivers: wood and biomass demands, burned area, afforestation and deforestation and forest management. Different forest models are applied depending on the existing stand, but at present it applies just to eucalyptus stands.…”
Section: Menu Simulatorsmentioning
confidence: 99%